2007
DOI: 10.1371/journal.pone.0001008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Spatial Patterns of Plant Recruitment Using Animal-Displacement Kernels

Abstract: For plants dispersed by frugivores, spatial patterns of recruitment are primarily influenced by the spatial arrangement and characteristics of parent plants, the digestive characteristics, feeding behaviour and movement patterns of animal dispersers, and the structure of the habitat matrix. We used an individual-based, spatially-explicit framework to characterize seed dispersal and seedling fate in an endangered, insular plant-disperser system: the endemic shrub Daphne rodriguezii and its exclusive disperser, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 48 publications
5
54
1
1
Order By: Relevance
“…In general, small seeds have usually longer retention times inside the digestive tract of dispersers than large seeds, which favours seed coat scarification (Traveset et al 2007 and references therein). In the present system, however, this does not seem to be the case, as retention time is independent of seed size (Santamaría et al 2007). In this latter work, the authors also found that larger seeds had higher chances of germination, but the effect of a larger size was reduced as retention time increased.…”
Section: Seed Ingestion By Lizards Versus Seed Deposition Effectscontrasting
confidence: 52%
See 3 more Smart Citations
“…In general, small seeds have usually longer retention times inside the digestive tract of dispersers than large seeds, which favours seed coat scarification (Traveset et al 2007 and references therein). In the present system, however, this does not seem to be the case, as retention time is independent of seed size (Santamaría et al 2007). In this latter work, the authors also found that larger seeds had higher chances of germination, but the effect of a larger size was reduced as retention time increased.…”
Section: Seed Ingestion By Lizards Versus Seed Deposition Effectscontrasting
confidence: 52%
“…Under controlled conditions, seeds from lizards' scats have a similar viability to those collected and depulped directly from plants . Seeds within the pulp do not emerge (at least during a period of 2 years; Santamaría et al 2007), which further points out to the importance of lizards in the de-inhibition effect (Traveset et al 2007). Postdispersal seed predation (mostly by rodents) is consistently high across years and localities .…”
Section: Study Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, our results suggest that the importance of disperser behavior may supersede the effects of disperser physiology and/or body size (similar to Spiegel andNathan 2007 andSantamarı´a et al 2007). The generality of this result is however questionable; instead, it should be taken to demonstrate that these factors play off against one another.…”
Section: Discussionmentioning
confidence: 70%